2015
DOI: 10.1016/j.alit.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Hymenoptera venom allergy in adults: The results of a very crowded city in Euroasia

Abstract: The prevalence of Hymenoptera sting reactions in our geographical region is comparable with other European studies. There is a need to increase the awareness of adrenaline in the emergency management of insect sting anaphylaxis and venom immunotherapy in the prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…A significant majority of the stings in our study group were attributed to Apis mellifera. This is consistent with previous studies conducted both in children [12,13] and adults [14] Compared to the present study, the rates of LLR and GCR were 4-to 5-fold higher in Izmir and Israeli studies [9,11]. The prevalence of SR found in our study was similar to rates reported in Ireland [10] and Izmir [11], but was approximately 5-fold higher in the Israeli study [9].…”
Section: Discussionsupporting
confidence: 92%
“…A significant majority of the stings in our study group were attributed to Apis mellifera. This is consistent with previous studies conducted both in children [12,13] and adults [14] Compared to the present study, the rates of LLR and GCR were 4-to 5-fold higher in Izmir and Israeli studies [9,11]. The prevalence of SR found in our study was similar to rates reported in Ireland [10] and Izmir [11], but was approximately 5-fold higher in the Israeli study [9].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of systemic reactions due to Hymenoptera stings in the general adult population was reported as between 1.2 and 4.3 % in Turkey, which was in line with representative studies from Europe and US (Gelincik et al 2015 ; Tankersley and Ledford 2015 ). However, the Quality of Life scores of patients with venom allergy and especially in those receiving VIT has not yet been evaluated in Turkey.…”
Section: Introductionsupporting
confidence: 87%
“…In our study, as well as the studies of Hirata et al, Seob Shin et al, and Bemanian et al, males were more frequent than females [ 18 – 20 ]. Gelincik et al found that males and females had the same prevalence of Hymenoptera venom allergies in Istanbul [ 21 ]. This difference may be attributed to the culture effect such as the influence of wearing a hijab on women in some countries, and the higher frequency of men in difficult jobs such as agriculture, animal husbandry, and beekeeping.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Yavuz et al, bronchial asthma and allergic rhinitis were identified in 25% and 17.1% of children with Hymenoptera venom allergies, respectively [ 25 ]. As mentioned in the literature, atopic diseases could not be considered a predictor of developing hypersensitivity to Hymenoptera sting [ 21 , 26 ]. Compared with individuals with mono-sensitization to Hymenoptera venom, an insignificantly higher prevalence of atopic diseases (28.8% vs. 42.1%) was observed in patients with dual-sensitization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%